The Effectiveness of the Bandongan Method in Enhancing Comprehension of Kitab Kuning - Wakib Kurniawan; Sudarno Sudarno (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to examine the effectiveness of the bandongan method in enhancing students’ comprehension of kitab kuning at Pondok Pesantren Bani Saiman Yusuf. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects consist of teachers and students involved in the learning process of kitab kuning. Data analysis is conducted thematically to depict patterns of teacher–student interaction, student engagement, and levels of understanding of kitab kuning materials. The findings indicate that the bandongan method is proven to be effective in improving students’ understanding of kitab kuning, particularly in terms of Arabic vocabulary mastery, textual meaning comprehension, and the ability to apply the teachings of the texts in daily religious practices. The key factors contributing to the success of the bandongan method include the teacher’s role as a facilitator, active student participation, and a systematic structure of material delivery. Although several challenges were identified such as variations in students’ Arabic literacy skills and decreased concentration during extended learning sessions strategies including material repetition, interactive question-and-answer sessions, and group discussions were found to effectively address these obstacles. Based on these findings, it can be concluded that the bandongan method remains relevant and effective within the context of modern Islamic boarding schools, particularly when integrated with active student engagement, teacher competence, and appropriate instructional management strategies. This study offers significant implications for the development of kitab kuning instructional methods in pesantren and contributes to the existing literature by reinforcing the effectiveness of traditional pedagogical approaches in religious education.